HUMOR DURING THE COVID 19 PANDEMIC - I Dewa Putu Wijana (fakultas sastra, 2021)
This paper intends to describe the humorous discourses that emerge during the corona virus diseases pandemic. Even though I am very sure that there are still very limited humorous phenomena used to be the material of joke during the pandemic, their existence is still considered very important in enriching the inventory of jocular discourses in the use of Indonesian or local languages. Accordingly, through the collection of data obtained from various sources, this paper try to classify types of humorous discourse can be found during the pandemic, and linguistic aspects exploited by the language speakers in creating their jokes.Key Words: Humour, Discourse, and Pandemic